Factors Affecting Palliative Care Development in Africa: In-Country Experts’ Perceptions in Seven Countries - Rhee, John Y.; Garralda, Eduardo; Namisango, Eve; Luyirika, Emmanuel; de Lima, Liliana; Powell, Richard A.; Robinson, Carole A.; Centeno, Carlos (Journal of Pain and Symptom Management, 2018)
Factors contributing to and impeding palliative care (PC) development in Africa can provide insights into current strategies for advancing PC.To identify key factors affecting PC development in African countries from in-country PC experts' perspectives.About 16 PC experts from seven African countries undertook semistructured interviews on PC development in their respective countries. An interpretive description approach was adopted, with data analyzed using constant comparison.Emerged themes included drivers, strengths, challenges, and aspirations for PC development in Africa. Drivers included advocates and pioneering organizations, HIV/AIDS, culture of caregiving, and the World Health Assembly PC resolution. Strengths included community health workers, the special role of nurses, diversity of services, and short training courses. Challenges included lack of PC education; lack of standardization in implementation; limited availability of and/or accessibility to morphine; poverty and disease burden; and lack of funding for PC. Aspirations included integration of PC, specialization in PC, nurse prescribing, and strong partnerships with Ministries of Health. Factors already highlighted in the literature were only briefly discussed.The key factors underpinning PC development in the seven countries contributed to the beginnings of PC in Africa, fueled by advocates who built on existing strengths to maximize opportunities. However, the current approach is at high risk in terms of its sustainability, and strategies for maximizing existing resources and growing infrastructure support are needed moving forward.
Keywords: Palliative care development, Africa, HIV, Sudan, Mozambique, South Africa, Cote d’Ivoire, Ghana, Namibia, Kenya